Plasma metabolites associated with colorectal cancer stage: Findings from an international consortium. Issue 12 (10th October 2019) - Geijsen, Anne J.M.R.; van Roekel, Eline H.; van Duijnhoven, Fränzel J.B.; Achaintre, David; Bachleitner‐Hofmann, Thomas; Baierl, Andreas; Bergmann, Michael M.; Boehm, Jürgen; Bours, Martijn J.L.; Brenner, Hermann; Breukink, Stéphanie O.; Brezina, Stefanie; et al.
Abstract : Colorectal cancer is the second most common cause of cancer‐related death globally, with marked differences in prognosis by disease stage at diagnosis. We studied circulating metabolites in relation to disease stage to improve the understanding of metabolic pathways related to colorectal cancer progression. We investigated plasma concentrations of 130 metabolites among 744 Stages I–IV colorectal cancer patients from ongoing cohort studies. Plasma samples, collected at diagnosis, were analyzed with liquid chromatography‐mass spectrometry using the Biocrates AbsoluteIDQ™ p180 kit. We assessed associations between metabolite concentrations and stage using multinomial and multivariable logistic regression models. Analyses were adjusted for potential confounders as well as multiple testing using false discovery rate (FDR) correction. Patients presented with 23, 28, 39 and 10% of Stages I–IV disease, respectively. Concentrations of sphingomyelin C26:0 were lower in Stage III patients compared to Stage I patients ( p FDR  < 0.05). Concentrations of sphingomyelin C18:0 and phosphatidylcholine (diacyl) C32:0 were statistically significantly higher, while citrulline, histidine, phosphatidylcholine (diacyl) C34:4, phosphatidylcholine (acyl‐alkyl) C40:1 and lysophosphatidylcholines (acyl) C16:0 and C17:0 concentrations were lower in Stage IV compared to Stage I patients ( p FDR  < 0.05). Our results suggest that metabolic pathways involving among others citrulline and histidine, implicated previously in colorectal cancer development, may also be linked to colorectal cancer progression. Abstract : What's new? Metabolomics is a sophisticated method for investigating whether the metabolite profile of a patient's blood, etc., may reflect the pathophysiological state of cancers and other diseases. In the present study, the authors analyzed circulating metabolites, seeking biomarkers related to colorectal cancer progression. Their results at various stages of colorectal cancer suggest that metabolic pathways involving citrulline, histidine, and other molecules that have been previously implicated in colorectal cancer development may also be linked to progression.